Reflecting culture diversity through the printed page: the case of OWK Zine - Panayides, Omiros (My University, 2017)
The politically unstable culture and the economic and social crisis that hit Cyprus—and the Mediterranean area in general—in 2013 have driven local art and design scenes to search for and find new non-traditional publishing forms. The current exploratory case will present the cultural diversity of Cyprus’ art and design scene through the experimental type and image of OWK zine. The case study will focus on the contributions that have been submitted to the zine so far, spanning one and a half years and numbering five issues (2015-2016). The results of this case study should allow us to better understand the importance of zines and independent publishing to the diverse art and design landscape of Cyprus.
Keywords: Zine; Culture; Diversity; Type and image